Penyusunan dan Validasi Lembar Kerja Peserta Didik Berbasis Literasi Sains Pada Materi Pencemaran Lingkungan - Aulia, Salma Fitri; Solikha, Maratus; Paujiah, Epa; Hadiansah, Hadiansah; Cahyono, Tri (Bioscientist : Jurnal Ilmiah Biologi, 2025)
The research conducted aims to formulate and assess the feasibility of the Student Worksheet (LKPD) based on science literacy on the topic of environmental pollution, specifically water pollution, which can be used to develop students’ knowledge about environmental pollution. The quality of the Student Worksheet refers to the criteria of validity, readability, and student responses to the Student Worksheet. This study uses a research and development (R&D) method with a 4D model consisting of stages: Define, Design, Development, without involving the Disseminate stage. Data collection was carried out through preliminary studies in the form of interviews, material and media validation questionnaires, as well as readability and student response questionnaires. The sequence of data analysis stages includes expert validation, readability testing by subject teachers and students, and student response questionnaires. This research was conducted at MA Negeri 1 Kota Bandung involving 16 students and 1 Biology teacher. The research results show that the developed LKPD is worthy, with a score of 72.66% from the material expert and 85.75% from the media expert, both of which fall into the eligible and very eligible categories. The overall average readability scores from the subject teacher and students were 80% and 91%, respectively. The response results from the students obtained a score of 89.16% with a very good interpretation. Thus, the developed LKPD can be used and supports the learning process in the classroom.